Pengaruh Kualitas Produk, Citra Merek Dan Promosi Terhadap Keputusan Pembelian Produk Skintific : Studi Kasus pada Konsumen Skintific di Toko Nusantara Kota Tebing Tinggi - Dian Purnama Sari; Dwi Nopitasari; Yula Anggi Kristiani (Economic Development Progress, 2025)
Marketing theories play an important role in explaining consumer behavior, especially theories related to purchasing decisions. The purpose of this study is to test the hypothesis regarding the influence of product quality, brand image, and promotion on purchasing decisions for Skintific products. The results of the study indicate that: product quality does not have a significant influence on purchasing decisions with a T-statistic value of -0.295; brand image influences purchasing decisions with a T-statistic value of 1.895; promotion has a significant influence on purchasing decisions with a T-statistic value of 9.779; and simultaneously, the three variables (product quality, brand image, and promotion) have a significant influence on purchasing decisions with a T-statistic value of 37.447. This study involved 64 respondents as samples, and data processing was carried out using SPSS software version 25.0.